2015
DOI: 10.4103/0253-7613.161265
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of skeletal muscle relaxant activity of aqueous extract of Nerium oleander flowers in Albino rats

Abstract: Objectives:Nerium oleander is traditionally used in various diseases because of its medicinal properties. One of its uses is in musculoskeletal disorder. The aim of the study was to evaluate the skeletal muscle relaxant activity of the aqueous extract of Nerium oleander flowers (AENOF) in albino rats in comparison with diazepam.Materials and Methods:A total of 20 Swiss albino rats aged 6–7 weeks, of either sex, weighing about 100–150 g, were taken, and after acute toxicity studies two different doses were sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 14 publications
1
8
1
Order By: Relevance
“…In contrast to the present study, Tirumalasetti et al (2015) reported skeletal muscle relaxant activity of aqueous extract of Nerium oleander flowers in albino rats. Also, Aparna et al (2015) reported significant muscle relaxant activity of aqueous leaf extract of Carica papaya.…”
Section: Muscle Relaxant Potentialcontrasting
confidence: 99%
“…In contrast to the present study, Tirumalasetti et al (2015) reported skeletal muscle relaxant activity of aqueous extract of Nerium oleander flowers in albino rats. Also, Aparna et al (2015) reported significant muscle relaxant activity of aqueous leaf extract of Carica papaya.…”
Section: Muscle Relaxant Potentialcontrasting
confidence: 99%
“…Several neuro-system (gamma‐aminobutyric acid, serotonin, and dopamine) dysregulation might be responsible for anxiety disorders ( Murrough et al, 2015 ). Motor coordination effect of the extract was observed by rotarod test, whereas the extracts showed a non-significant motor coordination effect which suggesting the antagonistic effect on GABA receptor ( Vikas and Payal, 2010 , Tirumalasetti et al, 2015 ), indicating CNS-depressant effect.…”
Section: Discussionmentioning
confidence: 99%
“…All the treatments were given continuously for a duration of 35 days and evaluation of behavioural parameters was performed on 1 st , 7 th , 14 th , 21 st , 28 th , and 35 th day of the experiment. Behavioural parameters includes postural instability,rearing behaviour (Woodlee et al, 2008;Cannon et al, 2009), catalepsy (Verma and Nehru, 2009), muscle activity (Tirumalasetti et al, 2015), locomotor activity (Bishnoi et al,2006) and body weight.…”
Section: Chemicalsmentioning
confidence: 99%